Knowledge and Nutritional Habits of Older Adults Regarding Immunity at Qena City - Chih, Jun; Emam, Nadia Omar; Fahmy, Hoda Diab; Alsayed, Mohamed Kamal; Hassan, Asmaa Kamal Hassan (2018)
Background: It is well-accepted that nutritional status plays a significant role in immune response especially among older adults. So, it is necessary to pay attention to their knowledge and nutritional habits.